2020
DOI: 10.3389/fonc.2020.00481
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Chemotherapy on Survival in Patients With Upper Urinary Tract Urothelial Carcinoma Undergoing Nephroureterectomy: A Population-Based Study

Abstract: Objectives: To estimate the stage-specific impact of perioperative chemotherapy on survival for upper urinary tract urothelial carcinoma (UTUC) patients treated with nephroureterectomy (NU).Methods: Overall, 7,278 UTUC patients treated with NU from 2004 to 2015 were identified within the SEER database. Kaplan-Meier plots were used to elucidate overall survival (OS) and cancer-specific survival (CSS) rates. Multivariable Cox regression analyses were used to test the impact of chemotherapy on survival rates, aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Goldberg, H et al stated that perioperative chemotherapy had no effect on cancer specific mortality in high-risk non-metastatic patients through SEER database [ 13 ]. However, Zhai, T. S. et al found that the beneficial effect of perioperative chemotherapy on OS was to be evident in pT3/pT4 and pN + patients but to reduce cancer-specific survival for pT1 and OS for pT2 patients [ 14 ]. For low-risk UTUC patients, the benefits of perioperative chemotherapy need to be carefully weighed against the risk.…”
Section: Discussionmentioning
confidence: 99%
“…Goldberg, H et al stated that perioperative chemotherapy had no effect on cancer specific mortality in high-risk non-metastatic patients through SEER database [ 13 ]. However, Zhai, T. S. et al found that the beneficial effect of perioperative chemotherapy on OS was to be evident in pT3/pT4 and pN + patients but to reduce cancer-specific survival for pT1 and OS for pT2 patients [ 14 ]. For low-risk UTUC patients, the benefits of perioperative chemotherapy need to be carefully weighed against the risk.…”
Section: Discussionmentioning
confidence: 99%
“…These results might suggest improved patient care in regard to tumor stage is one major prognostic factor after RNU [20]. Five-year CSS for patients undergoing RNU decreases from 89.3% for pT1 to 78.2% for pT2 [21]. Additionally, recurrence rate differs significantly already between noninvasive pTa/pTis and pT1 UTUC [22].…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have shown that perioperative chemotherapy improves the OS in patients with pT3/pT4 and pN+ disease but it reduces the CSS for those with pT1 and OS for those with pT2 disease. [ 28 ] Hence, perioperative chemotherapy may be an overkill in patients with low-risk disease, and hence, identifying high-risk patients with a preoperative NLR might help in reducing the over treatment with chemotherapy. Future research might explore the role of NLR as a factor to stratify high-risk patients and to identify those who can benefit from neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%